Effect of artesunate on apoptosis and autophagy in tamoxifen resistant breast cancer cells (TAM-R) - Ding, Xiaoqing; Yue, Wei; Chen, Haiyan (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Background: The antitumor effect of artesunate (ART) is well-recognized. To investigate the effect of ART on tamoxifen-resistant breast cancer cells (TAM-R) proliferation, apoptosis, and autophagy with TAM-R cells of breast cancer as objects of study, and to investigate whether ART could re-sensitize TAM-R cells to TAM therapy. Methods: Experiments were performed using TAM-R cell lines. Cell Death Detection ELISA kit was used to detect the level of apoptosis. Western blot and immunofluorescent staining analysis were conducted to detect autophagy and apoptosis related proteins in TAM-R cells. Results: After treated with ART, the proliferation activity of TAM-R cells was inhibited in a concentration-dependent manner. Increased apoptosis activity was detected in TAM-R cells when treated with ART. Compared with 10−6 M TAM monotherapy group, treatment group with ART and TAM in combination caused significant reduction in the levels of Bcl-2, XIAP, and Survivin proteins, and elevation of caspase-7. However, increased p53 proteins was not detected after ART treatment. No significant change was observed in autophagy proteins LC-3 and Beclin-1 among control, ART, TAM, and ART combined with TAM groups. Conclusions: The intervention of ART could not inhibit protective autophagy in TAM-R cells, however, possess potential in inducing apoptosis. In addition, as ART inhibit TAM-R cells growth in a dose-dependent manner, co-administration of 1 or 3 µM of ART with 10−6 M TAM might not be enough to re-sensitize TAM-R cells to TAM therapy.